What's in a crowd? Exploring crowdsourced versus traditional customer participation in the innovation process. Issue 13 (2nd September 2017) - Gruner, Richard L.; Power, Damien
ABSTRACT: This study explores the emerging crowdsourcing phenomenon, that is, the outsourcing of idea generation to the product users ('the crowd'), typically via online platforms to interact with many and diverse customers and glean valuable market insights. The study focuses on this phenomenon and the factors that determine the value of crowdsourced customer participation over more traditional market research methods. The authors present the results of an extensive, in-depth qualitative case-study analysis pertaining to the media industry. The authors find that crowdsourced customer participation is not consistently superior in enabling firms to discover how to serve their customers better. Instead, the results unearth a catalogue of seven interrelated value determinants that show where the boundaries of both crowdsourcing and traditional customer participation in innovation lie. These value determinants fall into three main categories: (1) innovation-specific value determinants, (2) firm-specific value determinants, and (3) managerial value determinants.